The role of motivation and cultural dialects in the in-group advantage for emotional vocalizations - Sauter, Disa (Frontiers in Psychology, 2013)
It is well established that nonverbal emotional communication via both facial and vocal information is more accurate when expresser and perceiver are from the same cultural group. Two accounts have been put forward to explain this finding: According to the dialect theory, culture-specific learning modulates the largely cross-culturally consistent expressions of emotions. Consequently, within-group signalling benefits from a better match of the "emotion dialect" of the expresser and perceiver. However, it has been proposed that the in-group advantage in emotion recognition could instead arise from motivational differences in the perceiver, with perceivers being more motivated when decoding signals from members of their own group. Two experiments addressed predictions from these accounts. Experiment 1 tested whether perceivers' ability to accurately judge the origin of emotional signals predicts the in-group advantage. For perceived group membership to affect the perceivers' motivation, they must be able to detect whether the signal is coming from an in-group or out-group member. Although an in-group advantage was found for in-group compared to out-group vocalisations, listeners were unable to reliably infer the group membership of the vocaliser. This result indicates that improved recognition of in-group signals can occur also when the perceiver is unable to judge whether signals were produced by in- or out-group members. Experiment 2 examined the effects of expected and actual group membership of signals on emotion recognition by manipulating both orthogonally. The actual origin of the stimulus was found to significantly affect emotion recognition, but the believed origin of the stimulus did not. Together these results support the notion that the in-group advantage is caused by culture-specific modulations of nonverbal expressions of emotions, rather than motivational factors.